Gray Matter and Regional Brain Activity Abnormalities in Subclinical Hypothyroidism - Zhang, Yang; Yang, Yaqiong; Tao, Bo; Lv, Qingguo; Lui, Su; He, Li (Frontiers in Endocrinology, 2021)
Abstract Background: Subclinical hypothyroidism (SCH) brain structure and resting state of functional activity have remained unexplored. Purpose: To investigate grey matter volume (GMV) and regional brain activity with the fractional amplitude of low-frequency fluctuations (fALFF) in subclinical hypothyroidism (SCH) patients before and after treatment. Material and Methods: We enrolled 54 SCH and 41 age-, sex- and education-matched controls. GMV and fALFF of SCH were compared with controls and between pre- and post-treatment within SCH group. Correlations of GMV and fALFF in SCH with thyroid function status and mood scales were assessed by multiple linear regression analysis. Results: Compared to controls, GMV in SCH was significantly decreased in Orbital part of inferior frontal, superior frontal, pre-/postcentral, inferior occipital, and temporal pole gyrus. FALFF values in SCH were significantly increased in right angular, left middle frontal, and left superior frontal gyrus. After treatment, there were no significant changes in GMV and the local brain function compared to pre-treatment, however the GMV and fALFF of the defective brain areas were improved. Additionally, decreased values of fALFF in left middle frontal gyrus were correlated with increased mood scales. Conclusion: In this study we found that patients with SCH, the gray matter volume in some brain areas were significantly reduced, and regional brain activity was significantly increased. After treatment, the corresponding structural and functional deficiencies had a tendency for improvement. These changes may reveal the neurological mechanisms of mood disorder in SCH patients.